2017
DOI: 10.1021/acs.cgd.6b01848
|View full text |Cite
|
Sign up to set email alerts
|

Co-crystal of Tramadol Hydrochloride–Celecoxib (ctc): A Novel API–API Co-crystal for the Treatment of Pain

Abstract: We have identified a co-crystal of tramadol hydrochloride−celecoxib (ctc; E-58425/MR308), a novel active pharmaceutical ingredient (API)−API co-crystal formed by an intrinsic 1:1 molecular ratio of rac-tramadol•HCl and celecoxib, which displays favorable physicochemical and dissolution profiles. Adequate treatment of pain represents an unmet medical need that is often addressed via combination therapy. API−API co-crystals represent a new approach with potential to improve physicochemical properties, bioavailab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
95
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 51 publications
(73 reference statements)
5
95
0
Order By: Relevance
“…In addition, CTC susp displayed comparable efficacy to the morphine and oxycodone in this model but with an improved safety profile . Intrinsic dissolution studies have shown that the release profiles of tramadol and celecoxib from the co‐crystal are modified compared with those from each reference drug . Such effects have the potential to optimize the PK profiles, and thus efficacy and safety, of each API in CTC.…”
Section: Introductionmentioning
confidence: 94%
“…In addition, CTC susp displayed comparable efficacy to the morphine and oxycodone in this model but with an improved safety profile . Intrinsic dissolution studies have shown that the release profiles of tramadol and celecoxib from the co‐crystal are modified compared with those from each reference drug . Such effects have the potential to optimize the PK profiles, and thus efficacy and safety, of each API in CTC.…”
Section: Introductionmentioning
confidence: 94%
“…Potential of co-crystal design for molecules with limited H-bonding functionalities was demonstrated on the example of propyphenazone [221]: NH 2 , OH, and CO 2 H functionalities were found to be the most likely groups to interact with O=C group, and eight novel co-crystals were obtained using co-formers containing OH or/and CO 2 H groups. Dicarboxylic acids [222] or anions [223,224] can be applied to co-crystallize two molecules, which do not form co-crystals. acids demonstrate that it is still difficult to predict co-crystallization of small rigid molecules using this method [219].…”
Section: Co-crystals Designmentioning
confidence: 99%
“…# 2018 International Union of Crystallography Drug-drug complexes, salts and cocrystals play important roles in developing combinational drugs and fixed-dose combinations (Tiekink & Zukerman-Schpector, 2017). Almansa et al (2017) reported that the cocrystal of tramadol hydrochloride-celecoxib presented favorable physicochemical and dissolution properties. Putra et al (2016) suggested that a salt-type multicomponent crystal composed of gliclazide (GLI) and metformin (MET) presented higher solubility for GLI and lower hygroscopicity for MET.…”
Section: Issn 2052-5206mentioning
confidence: 99%